MANFAAT YOUTUBE DALAM PENDIDIKAN PERTANIAN: APA PENDAPAT MAHASISWA? - Sabaruddin; Nahdiana; Andriansyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This research aims to describe the perceptions of students majoring in Agricultural Production Technology at Pangkep State Agricultural Polytechnic in utilizing YouTube as a learning resource and the effects resulting from accessing YouTube media. This type of research is qualitative descriptive and uses observation, interviews, and documentation of students as research informants representing four study programs, namely Plantation Crop Cultivation, Coffee Production and Processing, Food Crop Production Technology, and Horticultural Plant Production Technology. The research results show diverse student perceptions categorized as positive and negative perceptions. Students positively assess YouTube video content as a learning resource because it is informative and effective for acquiring knowledge and insights in the field of agriculture. YouTube is also considered an inspirational medium as students can channel their ideas and creativity as content creators and as a source of business learning for financial gain. Students also view YouTube negatively because it can disseminate information that is hoaxes and cannot be scientifically proven for its accuracy. The effects of YouTube as a learning resource for students include knowledge and insight (cognitive effects), changes in attitude (affective effects), and activities or actions (conative/behavioral effects).